Diagnosis and Successful Management of Acute Kidney Injury in a Leopard - Nayak, Yamini; Prajapati, Ankit S.; Parmar, Jignesh J. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
A male leopard was presented with lateral recumbency, dullness, depression, traumatic wound on the ventral abdomen and difficulty in urinating. Based on clinical examination and laboratory findings, the case was diagnosed as acute kidney injury and managed with fluid therapy, antibiotics and supportive treatment.